Building Teachers Digital Pedagogical Competence through Web-Based Interactive E-Module Training - Ni Nyoman Putri Nursanti; Sangputri Sidik; Intan Metrayani Sidauruk; Ashari Ramlan; Reni Kartini Kristin Dian Yunianti (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2026)
Background: requires teachers not only to be able to use technology, but also to design meaningful learning experiences through the pedagogical utilization of digital media. However, in practice, many teachers still use technology only at the operational level and have not optimally developed interactive digital teaching materials. In this context, training in the development of web-based interactive e-modules is essential as a strategy to strengthen teachers’ digital pedagogical competence. Purpose of Study: This study aimed to describe the process of strengthening teachers’ digital pedagogical competence through training in the development of web-based interactive e-modules and to identify changes in participants’ competence after participating in the training program. Methods: This study employed a quantitative approach using a one-group pretest-posttest design. The program was conducted in three stages: planning, implementation, and evaluation. The participants consisted of 25 senior high school teachers selected purposively. Data were collected through a digital pedagogical competence questionnaire, observations of the training process, and assessments of the e-module products, and were analyzed descriptively. Results: The findings revealed an improvement in teachers’ digital pedagogical competence, indicated by an increase in the average score from 58.96 in the pre-test to 81.44 in the post-test, with a gain of 22.6 points or an improvement of 38.2%. Competency enhancement was reflected in three main dimensions: digital instructional design, digital collaboration, and reflective and creative competence. The training also encouraged a shift in teachers’ orientation from technology users to more adaptive, creative, and reflective digital learning designers.